Mental health states and influencing factors of risky and problem drinking in South Korean female adolescents. (August 2020) - Jeon, Y.J.; Han, Y.J.; Choi, M.H.; Lee, J.S.; Lee, J.H.; Jo, S.H.; Kim, S.H.
Abstract: Objectives: Alcohol is one of the most used and abused psychoactive substances by adolescents. We investigated influencing factors of risky and problem drinking in Korean female adolescents. Study design: The study design used is a cross-sectional modeling. Methods: We used data from the 13th Korean Youth Risk Behavior Web-based Survey (KYRBS) conducted in 2017. KYRBS data were obtained from a stratified, multistage, clustered sample. Risky drinking was binge drinking and problem drinking was drinking with several conflicts association with alcohol consumption. Results: Among 62, 276 participants, the rates of current, risky, and problem drinking among all participants were 16.1%, 8.3%, and 6.1%, respectively. Although all of these rates were higher in males, risky and problem drinking rates among current female drinkers were higher than those of males (55.4 vs 48.5%, 38.9 vs 37.2%, respectively). Problem drinking was most strongly associated with risky drinking (adjusted odds ratio: 17.53 [95% confidence interval: 14.63–21.00]), similarly, risky drinking was most strongly associated with problem drinking in female current drinkers (17.76 [14.84–21.27]). Current smoking was the second strongest risk factor for risky and problem drinking in females (5.22 [3.92–6.95] and 2.93 [2.21–3.89], respectively). Conclusion: Many female adolescents in Korea drink alcohol in an unhealthy manner. The female risky and problem drinking rates among current drinkers were higher than those of males. Risky drinking and problem drinking was most significant influencing factor among females, reciprocally. Public education on abstinence in female adolescents is warranted. Highlights: Alcohol is one of the most used psychoactive substances by adolescents. All of current, risky, and problem drinking rates were higher in males. Risky and problem drinking rates among current female drinkers were higher. Problem and risky drinking were reciprocally the most important risk factors.